Analisis Regional Pengaruh Kapital Publik Manusia terhadap Perekonomian di Indonesia - Aimon, Hasdi (Jurnal Kajian Ekonomi, 2014)
Employees selection system an company determine ability of the employees in reaching employees work achivement which is flange to eficacy attainment of company target. for that, selection system is important and also have an effect forr attainment of employees work achievement an organization. that's also felt at PT. Pupuk Iskandar Muda (Persero), so that require to be done this research. this research aim to know the impact of selection system on employees work achievement at PT. Pupuk Iskandar Muda (persero). With simple random sampling method, taken counted 100 people from all population of company employees, with assumtion that population have the homogeneous character to be by responder or sample research. result of research indicate that corrrelation coefficient (R) equal to 0,659 is meaning that's are relation other influencing close enough between free variable of system select with variable tied employees work achivement.Later, then acquirement of value F count 18,262 with probabylity at level of significancy 0,000 indicating athat influence between system select with work achivement is significant.